2021
DOI: 10.1088/1361-6528/ac2847
|View full text |Cite
|
Sign up to set email alerts
|

Mixed metal ferrite (Mn0.6Zn0.4Fe2O4) intercalated g-C3N4 nanocomposite: efficient sunlight driven photocatalyst for methylene blue degradation

Abstract: Visible active mixed metal ferrite intercalated semiconductor photocatalyst Mn 0.6 Zn 0.4 Fe 2 O 4 /g-C 3 N 4 was prepared via facile hydrothermal and liquid assembly method for methylene blue (MB) dye degradation. The prepared samples were well characterized in term of their functional groups, crystallinity, elemental analysis, surface morphology using Fourier transform infrared spectroscopy, x-ray diffraction spectroscopy, energy dispersive x-ray, and scanning electron microscopy, respectively. The optical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 66 publications
1
2
0
Order By: Relevance
“…Tese results confrmed the formation of nanoparticles since the average crystal size ranged between 4.63 and 8.51 nm. Tese values were comparable to the average crystallite size results obtained by Saeed et al for Mn 0.6 Zn 0.4 Fe 2 O 4 /g-C 3 N 4 photocatalyst which ranged between 5.8 and 6.96 nm [47].…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Tese results confrmed the formation of nanoparticles since the average crystal size ranged between 4.63 and 8.51 nm. Tese values were comparable to the average crystallite size results obtained by Saeed et al for Mn 0.6 Zn 0.4 Fe 2 O 4 /g-C 3 N 4 photocatalyst which ranged between 5.8 and 6.96 nm [47].…”
Section: Resultssupporting
confidence: 89%
“…It can be observed that ZnFe 2 O 4 particles consisted of almost spherical nodules with a diameter ranging between 30.71 nm and 50.97 nm. Tese particles are highly agglomerated and interlock to form clusters, which could be attributed to the magnetic character of spinel ferrites [47,51].…”
Section: Morphology and Chemical Compositionmentioning
confidence: 99%
“…Also, a band at 2355 cm −1 can be accredited to adsorbed carbon dioxide in all the samples [43]. The FT-IR spectra of the Ni/GZ and Mn/GZ composites contain the peaks corresponding to both ZnO and g-C3N4, signifying that the composites were formed successfully [43][44][45].…”
Section: Ftir Analysismentioning
confidence: 92%